Représentations des migrants et de la migration dans la fiction grecque contemporaine - Diamanti Anagnostopoulou (Cahiers Balkaniques)
In this presentation, we explore a corpus of contemporary neo-Hellenic fiction books (novels and narratives) that address the contemporary migration crisis. Their themes focus on the waves of migrants in recent years and their impact on neo-Hellenic society. The problematic of the paper revolves around the following questions:- How do these fictions address the phenomenon of migration and in what manner?- What is the relationship between the real and the imaginary, reality and fiction, the relationship between the real world and the fictional universe?- How do these books address the encounter of peoples, the image of the Other, the “xenos”, and what national and social stereotypes are included?What questions are raised by the authors and what conclusions can be drawn regarding the transmission of the current migration phenomenon and the notion of otherness? To examine the above questions, we will use imagology theory, semiotics of stereotype, and literary theory concerning the universe of fiction and its relationship with reality.